Pengaruh Campuran Baja Ringan Terhadap Kekuatan Beton - Rewilla Aryanti; Eko Walujodjati (Jurnal Konstruksi, 2022)
Concrete has a high compressive strength but has a low tensile strength, therefore it is necessary to have additional materials aimed at increasing the tensile strength. The use of additives in concrete technology has long been developed. Concrete has a tensile strength of 8%–15% of compressive strength. Some effort is required to increase the tensile strength. One of them is the addition of additional materials, namely pieces of mild steel. The purpose of this study was to determine the compressive strength and split tensile strength of concrete after the addition of mild steel variations of 0%, 10%, 15% and 20%. The design concrete quality is 20 MPa and the concrete age is l4 and 28 days. The specimens for compressive strength and splitting tensile strength of concrete are cylinders with a diameter of 15 cm and a height of 30 cm. The research method used was an experiment with a research time of two months. The compressive strength test results have increased and decreased. The biggest increase was in the 15% mixture with a percentage increase of 46.33% and an average compressive strength value of 12.162 N/mm2 at 14 days of concrete age, while the highest average compressive strength was in a mixture of 0% or normal concrete with a strength value compressive strength of 13.859 N/mm2 concrete aged 28 days. The largest average split tensile strength test results were in a 10% mixture with a split tensile strength value of 2,183 MPa and a percentage increase of 24.09%. The optimum addition of mild steel that produces maximum tensile strength is 10%.